Word as censor - Garg, Mridula (2000)
Literature has always found escape routes from the power polemics by giving new multiple meanings to words. Over the ages the dominant power structures of the day have attempted to control language by placing restriction of words - by blotting them out, reducing the shades of meaning they could have or divorcing a word from meaning. Can literature, along with the other visual and plastic arts, find escape routes through the subtle forms of censorship practised today? - Reproduced
Keywords: Censorship